Cyclic Microwave-Assisted Metathetic Synthesis and Characterization of Ag-SrWO4/Zeolite Composites - Sung Lim, Chang (Asian Journal of Chemistry, 2014)
Silver incorporated SrWO4/zeolite (Ag-SrWO4/zeolite) composites were successfully synthesized by a cyclic microwave-assisted metathetic route followed by heat treatment. The crystallized Ag-SrWO4/zeolite composites were formed at 600 ºC for 3 h, showing a well immobilized morphology with particle sizes of 3-5 μm. The synthesized Ag-SrWO4/zeolite composites were characterized by scanning electron microscopy, energy-dispersive X-ray spectroscopy and Fourier transform infrared spectroscopy. The optical properties were examined using photoluminescence emission and Raman spectroscopy.